Economics of Carnation Cut Flower Production in Kathmandu Valley, Nepal - Bhandari, Pawan Singh; Bhattarai, Thakur (Economic Journal of Development Issues, 2020)
Carnation is an important cut flower commercially traded in Kathmandu Valley. It has high demand in the Kathmandu Valley’s floriculture market due to its physical characteristics and its suitability to be used singly or in combination with other flowers. This examines the economics of carnation cut flower production in Kathmandu Valley. The data for the study was collected from a sample of 15 carnation cut flower producers in Kathmandu Valley. Simple random sampling technique was employed to select the respondents. Information from the respondents collected through semi-structured interview schedule. Data collected through personal interview and secondary sources was analyzed by applying descriptive statistical tools. Data analysis focused mainly on the costs and returns from the carnation production, trends in production and prices, present problems in production and future prospects of carnation production in Kathmandu Valley. The findings revealed that the profits from carnation cut flower were satisfactory to the producers. However, there were ample areas of improvements in the production system. Given the high degree of demand and increasing trend of imports, concerted efforts must be made to reverse the situation and become self-reliant in fulfilling the demand for carnation cut flowers alongside exporting to other countries in the future.